P213 RAID-IBS Diagnosis: A new non-invasive method to support Irritable Bowel Syndrome diagnosis. (16th January 2018) - Amoedo, J; Ramió-Pujol, S; Bahí, A; Oliver, L; Torrealba, L; Clos, A; Cañete, F; Mañosa, M; Ibáñez-Sanz, G; Gilabert, P; Serra-Pagès, M; Miquel-Cusachs, J O; et al.
Abstract: Background: Irritable Bowel Syndrome (IBS) is a functional disorder affecting up to 10% of world population. Diagnostics is mainly based on clinical parameters. However inflammatory bowel disease (IBD) can share IBS symptomatology, which complicates the correct diagnosis. Colonoscopy, is the gold standard for differential diagnosis in spite of costs and risks. Currently, non-invasive markers such as Fecal Calprotectin (FC) are also used, but more reliable tools are needed to avoid unnecessary colonoscopies in IBS patients. GoodGut is developing a new method based on fecal microbiota ( RAID-IBS Diagnosis ) to help distinguishing between IBS and IBD. The aim of this study was to assess the accuracy of RAID-IBS Diagnosis as compared with FC. Methods: A cohort of 18 IBS and 53 IBD patients were recruited from five Gastroenterology departments in Catalonia. All IBS patients complained of diarrhoea, met Rome IV criteria and had a previous colonoscopy with no inflammatory signs. On the other hand, al IBD patients had mucosal inflammation at colonoscopy and showed increased clinical activity indexes (Harvey-Bradshaw index and Partial Mayo Index). A stool sample from each subject was used to determine FC and RAID-IBS Diagnosis. Results: RAID-IBS Diagnosis discriminates IBS from IBD patients with a very high sensitivity with values up to 94.4% for IBS, and a very high specificity with values up to 92.2% for IBD. When the usefulness of FC was evaluated in same cohort of patients with a predetermined cut-off of 50 µg/g, sensitivity was 50.0% and specificity 90.2%. These results support a substantial increase in the positive predictive value (PPV) and negative predictive value (NPV) by RAID-IBS Diagnosis : 80.9% and 97.9%, respectively, in comparison to that obtained by FC (64.3% and 83.6%, respectively). Conclusions: To date, RAID-IBS Diagnosis is the highest accuracy biomarker to discriminate IBS from IBD; sensitivity, specificity, PPV and NPV are notably better to that obtained with FC. The use of this new tool for IBS diagnosis, might allow us to reduce unnecessary colonoscopies in IBS patients in an 88.8%.